A kind of high corrosion-resistant stainless steel and its processing technology
Through solid solution treatment, pretreatment and gas nitriding processes, the corrosion resistance of stainless steel is improved, and the problem of insufficient corrosion resistance of traditional stainless steel in special environments is solved, and higher corrosion resistance is achieved.
Patent Information
- Application Number
- CN202411806243.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-12-10
AI Technical Summary
Traditional stainless steel materials have insufficient corrosion resistance in certain special environments, such as chemical treatment, marine engineering and high temperature and high humidity environments, which limits their application in high-demand fields.
The corrosion resistance of stainless steel is improved through solid solution treatment, pretreatment and gas nitriding processes. Specific steps include: solution treatment and rolling stainless steel strips, ultrasonic cleaning and electrodeposition coatings, nitrogen blow-drying and heat treatment, and finally gas nitriding at high temperatures.
It significantly improves the surface hardness and corrosion resistance of stainless steel, and enhances its application capabilities in high-demand environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of stainless steel, in particular to high corrosion-resistant stainless steel and a processing technology thereof. Background Art
[0002] With the continuous advancement of industrial technology, the performance requirements of stainless steel materials are also increasing. In many industrial applications, corrosion resistance, strength and precision are the key factors that determine the quality of stainless steel materials. Although traditional stainless steel materials have good mechanical strength, they still have insufficient corrosion resistance in certain special environments, such as chemical treatment, marine engineering, and high temperature and high humidity environments. This limits the application of stainless steel materials in some high-demand fields.
[0003] In order to solve the above problems and improve the corrosion resistance of stainless steel materials, the present invention provides a high corrosion-resistant stainless steel and a processing technology thereof. Summary of the invention
[0004] The object of the present invention is to provide a high corrosion-resistant stainless steel and a processing technology thereof to solve the problems raised in the prior art.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A processing technology for highly corrosion-resistant stainless steel comprises the following steps:
[0007] Step 1: subjecting the stainless steel strip to solid solution treatment, flattening, and rolling to obtain a rolled stainless steel strip;
[0008] Step 2: placing the rolled stainless steel strip in a cleaning solution, setting the temperature to 55-60°C, and ultrasonically cleaning for 3-5 minutes; washing again with deionized water, and drying with nitrogen; coating the surface with an antioxidant mixed solution; electroplating with direct current electrodeposition for 2-3 minutes in an electrodeposition solution, cleaning the surface, and then heat treating under nitrogen for 20-25 minutes to obtain a pretreated stainless steel strip;
[0009] Step 3: gas nitriding the pretreated stainless steel strip at a working pressure of 0.01 MPa and a temperature of 450°C for 18-20 hours to obtain a highly corrosion-resistant stainless steel;
[0010] The electrodeposition solution comprises the following components: 200-210 g / L of nickel chloride, 20-22 g / L of cerium chloride, 20-23 g / L of nano silicon oxide, 5-7 g / L of nano carbon nitride-organic skeleton composite material, 3-4 g / L of potassium fluorozirconate, 2-2.5 g / L of citric acid, 60-65 mL / L of hydrochloric acid, and the rest is water.
[0011] More optimally, the preparation method of the nano carbon nitride-organic skeleton composite material is: take the organic skeleton material and Tris-HCl buffer, ultrasonically disperse to obtain a dispersion; take dopamine hydrochloride and Tris-HCl buffer, stir evenly, add the dispersion, ultrasonicate for 20-22 minutes, then stir for 6-7 hours, add modified nano carbon nitride, stir for 2-3 hours, add sulfonic acid polyaspartic acid, heat to 45-50°C, react for 5-6 hours, wash, filter, and dry to obtain the nano carbon nitride-organic skeleton composite material.
[0012] More optimally, the preparation method of the sulfonic acid polyaspartic acid is: take maleic anhydride, sodium 2-aminoethanesulfonate, and ammonium carbonate, mix them evenly, add deionized water, irradiate for 5-6 minutes, add sodium hydroxide solution, stir evenly, irradiate for 3-4 minutes, use hydrochloric acid to adjust the pH value of the solution to 2-3, precipitate, filter, and dry to obtain sulfonic acid polyaspartic acid.
[0013] More optimally, the preparation method of the modified nano carbon nitride is: take melamine, heat it to 545-555°C, calcine it for 2-2.5h, cool it to 25-30°C, grind it, add it to anhydrous ethanol, stir it evenly, add octadecyltrichlorosilane, stir it for 3-4h, centrifuge it, wash it, remove the supernatant, and dry it to obtain modified nano carbon nitride.
[0014] More optimally, the preparation method of the organic framework material is: take sodium fumarate and deionized water, stir evenly to obtain a sodium fumarate solution; take aluminum nitrate nonahydrate and deionized water, stir evenly, add the sodium fumarate solution dropwise, continue stirring for 10-15 minutes, filter, wash, and dry to obtain the organic framework material.
[0015] More optimally, the cleaning solution includes the following components: 3wt% citric acid, 9wt% phosphoric acid, and the remainder water.
[0016] More optimally, the antioxidant mixture includes the following ingredients: 3.5wt% sodium chloride, 3.5wt% citric acid, 2wt% L-cysteine, and the rest is water.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] 1. The present invention improves the gas nitriding efficiency through solid solution treatment and pretreatment, and enhances the surface hardness and corrosion resistance of corrosion-resistant stainless steel.
[0019] The invention processes stainless steel by using an electroplating liquid, and electroplates a coating containing nickel, cerium, nano silicon dioxide, nano carbon nitride-organic skeleton composite material and zirconium on the surface of the stainless steel, thereby enhancing the corrosion resistance of the corrosion-resistant stainless steel.
[0020] 2. The present invention uses melamine to calcine at high temperature to prepare an anti-corrosion nano carbon nitride with a lamellar structure, and then uses octadecyltrichlorosilane to modify it to enhance the hydrophobicity and dispersibility of the nano carbon nitride;
[0021] The polyaspartic acid is modified with sulfonic acid groups. The introduction of sulfonic acid groups can improve the dispersion performance of the polyaspartic acid. The nano-carbon nitride-organic skeleton composite material is modified with sulfonic acid polyaspartic acid, thereby improving the dispersion effect of the nano-carbon nitride-organic skeleton composite material.
[0022] 3. The present invention adds potassium fluorozirconate to the electrodeposition solution, and the addition of polyaspartic acid on the nano carbon nitride-organic skeleton composite material promotes the deposition of zirconium element, so that zirconium element is deposited on the surface of the stainless steel strip, further enhancing the corrosion resistance of the stainless steel strip. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] There is no special restriction on the purchase manufacturers of all raw materials involved in the present invention, and illustratively include: nano-silicon dioxide: particle size: 20nm, model: TSP-L12, which can be purchased from Nanjing Tianxing New Materials Co., Ltd.; polyaspartic acid: model: T25164, which can be purchased from Shanghai Yuanye Biotechnology Co., Ltd.
[0025] Embodiment 1: A processing technology for highly corrosion-resistant stainless steel, comprising the following steps:
[0026] Step 1: Preparation of modified nano carbon nitride:
[0027] Take 6g of melamine, heat to 550°C, calcine for 2.3h, cool to 28°C, grind, add to 500mL of anhydrous ethanol, stir evenly, add 2.5g of octadecyltrichlorosilane, stir for 3.5h, centrifuge, wash, remove the supernatant, and dry to obtain modified nano carbon nitride;
[0028] Step 2: Preparation of sulfonic acid polyaspartic acid:
[0029] Take 10g of maleic anhydride, 7.5g of sodium 2-aminoethanesulfonate, and 6g of ammonium carbonate, mix them evenly, add 30mL of deionized water, irradiate them at 300W microwave power for 5.5min, add 30mL of 2mol / L sodium hydroxide solution, stir evenly, irradiate them at 300W microwave power for 3.5min, adjust the pH value of the solution to 2.5 with 36% hydrochloric acid, precipitate, filter, and dry to obtain sulfonic polyaspartic acid;
[0030] Step 3: Preparation of organic framework materials:
[0031] Take 8g of sodium fumarate and 125mL of deionized water, stir evenly to obtain a sodium fumarate solution; take 9.5g of aluminum nitrate nonahydrate and 125mL of deionized water, stir evenly, add the sodium fumarate solution dropwise, continue stirring for 12min, filter, wash, and dry to obtain an organic framework material;
[0032] Step 4: Preparation of nano carbon nitride-organic framework composite materials:
[0033] Take 1g of organic framework material and 100mL of Tris-HCl buffer, and perform ultrasonic dispersion to obtain a dispersion; take 1.4g of dopamine hydrochloride and 200mL of Tris-HCl buffer, stir evenly, add the dispersion, perform ultrasonic dispersion for 21min, and then stir for 6.5h, add 0.5g of modified nano carbon nitride, stir for 2.5h, add 3g of sulfonic polyaspartic acid, heat to 47°C, react for 5.5h, wash, filter, and dry to obtain a nano carbon nitride-organic framework composite material;
[0034] Step 5: Preparation of high corrosion resistant stainless steel:
[0035] S1: subjecting the stainless steel strip to solid solution treatment, flattening, and rolling to obtain a rolled stainless steel strip;
[0036] S2: Place the rolled stainless steel strip in the cleaning solution, set the temperature to 57°C, and perform ultrasonic cleaning for 4 minutes; rinse again with deionized water and blow dry with nitrogen; 2 Apply the antioxidant mixture in an amount of coating;
[0037] In the electrodeposition solution, set the temperature to 42°C and the current density to 10A / dm -2 , direct current electrodeposition plating for 2.5 min, cleaning the surface, and then heat treating at 200 °C for 22 min in nitrogen to obtain a pretreated stainless steel strip;
[0038] The cleaning solution includes the following components: 3wt% citric acid, 9wt% phosphoric acid, and the remainder water;
[0039] The antioxidant mixture comprises the following ingredients: 3.5wt% sodium chloride, 3.5wt% citric acid, 2wt% L-cysteine, and the remainder is water;
[0040] The electrodeposition solution comprises the following components: 200 g / L nickel chloride, 20 g / L cerium chloride, 20 g / L nano silicon dioxide, 5 g / L nano carbon nitride-organic framework composite material, 3 g / L potassium fluorozirconate, 2 g / L citric acid, 60 mL / L hydrochloric acid, and the rest is water;
[0041] S3: The pretreated stainless steel strip is gas nitrided at a working gas pressure of 0.01 MPa and a temperature of 450° C. for 19 hours to obtain a highly corrosion-resistant stainless steel.
[0042] Embodiment 2: A processing technology for highly corrosion-resistant stainless steel, comprising the following steps:
[0043] Step 1: Preparation of modified nano carbon nitride:
[0044] Take 6g of melamine, heat to 545℃, calcine for 2h, cool to 25℃, grind, add to 500mL of anhydrous ethanol, stir evenly, add 2.5g of octadecyltrichlorosilane, stir for 3h, centrifuge, wash, remove the supernatant, and dry to obtain modified nano carbon nitride;
[0045] Step 2: Preparation of sulfonic acid polyaspartic acid:
[0046] Take 10g of maleic anhydride, 7.5g of sodium 2-aminoethanesulfonate, and 6g of ammonium carbonate, mix them evenly, add 30mL of deionized water, irradiate them at 300W microwave power for 5min, add 30mL of 2mol / L sodium hydroxide solution, stir evenly, irradiate them at 300W microwave power for 3min, adjust the pH value of the solution to 2 with 35% hydrochloric acid, precipitate, filter, and dry to obtain sulfonic polyaspartic acid;
[0047] Step 3: Preparation of organic framework materials:
[0048] Take 8g of sodium fumarate and 125mL of deionized water, stir evenly to obtain a sodium fumarate solution; take 9.5g of aluminum nitrate nonahydrate and 125mL of deionized water, stir evenly, add the sodium fumarate solution dropwise, continue stirring for 10min, filter, wash, and dry to obtain an organic framework material;
[0049] Step 4: Preparation of nano carbon nitride-organic framework composite materials:
[0050] Take 1g of organic framework material and 100mL of Tris-HCl buffer, and perform ultrasonic dispersion to obtain a dispersion; take 1.4g of dopamine hydrochloride and 200mL of Tris-HCl buffer, stir evenly, add the dispersion, perform ultrasonic dispersion for 20min, and then stir for 6h, add 0.5g of modified nano carbon nitride, stir for 2h, add 3g of sulfonic polyaspartic acid, heat to 45°C, react for 5h, wash, filter, and dry to obtain a nano carbon nitride-organic framework composite material;
[0051] Step 5: Preparation of high corrosion resistant stainless steel:
[0052] S1: subjecting the stainless steel strip to solid solution treatment, flattening, and rolling to obtain a rolled stainless steel strip;
[0053] S2: Place the rolled stainless steel strip in the cleaning solution, set the temperature to 55°C, and perform ultrasonic cleaning for 3 minutes; rinse again with deionized water and blow dry with nitrogen; 2 Apply the antioxidant mixture in an amount of coating;
[0054] In the electrodeposition solution, set the temperature to 40°C and the current density to 10A / dm -2 , direct current electrodeposition plating for 2 min, cleaning the surface, and then heat treating at 200 °C in nitrogen for 20 min to obtain a pretreated stainless steel strip;
[0055] The cleaning solution includes the following components: 3wt% citric acid, 9wt% phosphoric acid, and the remainder water;
[0056] The antioxidant mixture comprises the following ingredients: 3.5wt% sodium chloride, 3.5wt% citric acid, 2wt% L-cysteine, and the remainder is water;
[0057] The electrodeposition solution comprises the following components: 200 g / L nickel chloride, 20 g / L cerium chloride, 20 g / L nano silicon dioxide, 5 g / L nano carbon nitride-organic framework composite material, 3 g / L potassium fluorozirconate, 2 g / L citric acid, 60 mL / L hydrochloric acid, and the rest is water;
[0058] S3: The pretreated stainless steel strip is gas nitrided at a working gas pressure of 0.01 MPa and a temperature of 450° C. for 18 hours to obtain a highly corrosion-resistant stainless steel.
[0059] Embodiment 3: A processing technology for highly corrosion-resistant stainless steel, comprising the following steps:
[0060] Step 1: Preparation of modified nano carbon nitride:
[0061] Take 6g of melamine, heat to 555°C, calcine for 2.5h, cool to 30°C, grind, add to 500mL of anhydrous ethanol, stir evenly, add 2.5g of octadecyltrichlorosilane, stir for 4h, centrifuge, wash, remove the supernatant, and dry to obtain modified nano carbon nitride;
[0062] Step 2: Preparation of sulfonic acid polyaspartic acid:
[0063] Take 10g of maleic anhydride, 7.5g of sodium 2-aminoethanesulfonate, and 6g of ammonium carbonate, mix them evenly, add 30mL of deionized water, irradiate them at 300W microwave power for 6min, add 30mL of 2mol / L sodium hydroxide solution, stir evenly, irradiate them at 300W microwave power for 4min, adjust the pH value of the solution to 3 with 37% hydrochloric acid, precipitate, filter, and dry to obtain sulfonic polyaspartic acid;
[0064] Step 3: Preparation of organic framework materials:
[0065] Take 8g of sodium fumarate and 125mL of deionized water, stir evenly to obtain a sodium fumarate solution; take 9.5g of aluminum nitrate nonahydrate and 125mL of deionized water, stir evenly, add the sodium fumarate solution dropwise, continue stirring for 15min, filter, wash, and dry to obtain an organic framework material;
[0066] Step 4: Preparation of nano carbon nitride-organic framework composite materials:
[0067] Take 1g of organic framework material and 100mL of Tris-HCl buffer, and perform ultrasonic dispersion to obtain a dispersion; take 1.4g of dopamine hydrochloride and 200mL of Tris-HCl buffer, stir evenly, add the dispersion, perform ultrasonic dispersion for 22min, and then stir for 7h, add 0.5g of modified nano carbon nitride, stir for 3h, add 3g of sulfonic polyaspartic acid, heat to 50°C, react for 6h, wash, filter, and dry to obtain a nano carbon nitride-organic framework composite material;
[0068] Step 5: Preparation of high corrosion resistant stainless steel:
[0069] S1: subjecting the stainless steel strip to solid solution treatment, flattening, and rolling to obtain a rolled stainless steel strip;
[0070] S2: Place the rolled stainless steel strip in the cleaning solution, set the temperature to 60°C, and perform ultrasonic cleaning for 5 minutes; rinse again with deionized water and blow dry with nitrogen; 2 Apply the antioxidant mixture in an amount of coating;
[0071] In the electrodeposition solution, set the temperature to 45°C and the current density to 10A / dm -2, direct current electrodeposition plating for 3 min, cleaning the surface, and then heat treating at 200 °C for 25 min in nitrogen to obtain a pretreated stainless steel strip;
[0072] The cleaning solution includes the following components: 3wt% citric acid, 9wt% phosphoric acid, and the remainder water;
[0073] The antioxidant mixture comprises the following ingredients: 3.5wt% sodium chloride, 3.5wt% citric acid, 2wt% L-cysteine, and the remainder is water;
[0074] The electrodeposition solution comprises the following components: 200 g / L nickel chloride, 20 g / L cerium chloride, 20 g / L nano silicon dioxide, 5 g / L nano carbon nitride-organic framework composite material, 3 g / L potassium fluorozirconate, 2 g / L citric acid, 60 mL / L hydrochloric acid, and the rest is water;
[0075] S3: The pretreated stainless steel strip is gas nitrided at a working gas pressure of 0.01 MPa and a temperature of 450° C. for 20 hours to obtain a highly corrosion-resistant stainless steel.
[0076] Comparative Example 1: No nano carbon nitride is added, and the rest is the same as Example 1:
[0077] Step 1: Preparation of sulfonic acid polyaspartic acid:
[0078] Take 10g of maleic anhydride, 7.5g of sodium 2-aminoethanesulfonate, and 6g of ammonium carbonate, mix them evenly, add 30mL of deionized water, irradiate them at 300W microwave power for 5.5min, add 30mL of 2mol / L sodium hydroxide solution, stir evenly, irradiate them at 300W microwave power for 3.5min, adjust the pH value of the solution to 2.5 with 36% hydrochloric acid, precipitate, filter, and dry to obtain sulfonic polyaspartic acid;
[0079] Step 2: Preparation of organic framework materials:
[0080] Take 8g of sodium fumarate and 125mL of deionized water, stir evenly to obtain a sodium fumarate solution; take 9.5g of aluminum nitrate nonahydrate and 125mL of deionized water, stir evenly, add the sodium fumarate solution dropwise, continue stirring for 12min, filter, wash, and dry to obtain an organic framework material;
[0081] Step 3: Preparation of modified organic framework composite materials:
[0082] Take 1g of organic skeleton material and 100mL of Tris-HCl buffer, and perform ultrasonic dispersion to obtain a dispersion; take 1.4g of dopamine hydrochloride and 200mL of Tris-HCl buffer, stir evenly, add the dispersion, perform ultrasonic dispersion for 21min, and then stir for 6.5h, add 3g of sulfonic acid polyaspartic acid, heat to 47°C, react for 5.5h, wash, filter, and dry to obtain a modified organic skeleton composite material;
[0083] Step 4: Preparation of high corrosion resistant stainless steel:
[0084] S1: subjecting the stainless steel strip to solid solution treatment, flattening, and rolling to obtain a rolled stainless steel strip;
[0085] S2: Place the rolled stainless steel strip in the cleaning solution, set the temperature to 57°C, and perform ultrasonic cleaning for 4 minutes; rinse again with deionized water and blow dry with nitrogen; 2 Apply the antioxidant mixture in an amount of coating;
[0086] In the electrodeposition solution, set the temperature to 42°C and the current density to 10A / dm -2 , direct current electrodeposition plating for 2.5 min, cleaning the surface, and then heat treating at 200 °C for 22 min in nitrogen to obtain a pretreated stainless steel strip;
[0087] The cleaning solution includes the following components: 3wt% citric acid, 9wt% phosphoric acid, and the remainder water;
[0088] The antioxidant mixture comprises the following ingredients: 3.5wt% sodium chloride, 3.5wt% citric acid, 2wt% L-cysteine, and the remainder is water;
[0089] The electrodeposition solution comprises the following components: 200 g / L nickel chloride, 20 g / L cerium chloride, 20 g / L nano silicon dioxide, 5 g / L modified organic framework composite material, 3 g / L potassium fluorozirconate, 2 g / L citric acid, 60 mL / L hydrochloric acid, and the rest is water;
[0090] S3: The pretreated stainless steel strip is gas nitrided at a working gas pressure of 0.01 MPa and a temperature of 450° C. for 19 hours to obtain a highly corrosion-resistant stainless steel.
[0091] Comparative Example 2: Polyaspartic acid is not modified with sulfonic acid groups, and the rest is the same as Example 1:
[0092] Step 1: Preparation of modified nano carbon nitride:
[0093] Take 6g of melamine, heat to 550°C, calcine for 2.3h, cool to 28°C, grind, add to 500mL of anhydrous ethanol, stir evenly, add 2.5g of octadecyltrichlorosilane, stir for 3.5h, centrifuge, wash, remove the supernatant, and dry to obtain modified nano carbon nitride;
[0094] Step 2: Preparation of organic framework materials:
[0095] Take 8g of sodium fumarate and 125mL of deionized water, stir evenly to obtain a sodium fumarate solution; take 9.5g of aluminum nitrate nonahydrate and 125mL of deionized water, stir evenly, add the sodium fumarate solution dropwise, continue stirring for 12min, filter, wash, and dry to obtain an organic framework material;
[0096] Step 3: Preparation of nano carbon nitride-organic framework composite materials:
[0097] Take 1g of organic framework material and 100mL of Tris-HCl buffer, and perform ultrasonic dispersion to obtain a dispersion; take 1.4g of dopamine hydrochloride and 200mL of Tris-HCl buffer, stir evenly, add the dispersion, perform ultrasonic dispersion for 21min, and then stir for 6.5h, add 0.5g of modified nano carbon nitride, stir for 2.5h, add 3g of polyaspartic acid, heat to 47°C, react for 5.5h, wash, filter, and dry to obtain a nano carbon nitride-organic framework composite material;
[0098] Step 4: Preparation of high corrosion resistant stainless steel:
[0099] S1: subjecting the stainless steel strip to solid solution treatment, flattening, and rolling to obtain a rolled stainless steel strip;
[0100] S2: Place the rolled stainless steel strip in the cleaning solution, set the temperature to 57°C, and perform ultrasonic cleaning for 4 minutes; rinse again with deionized water and blow dry with nitrogen; 2 Apply the antioxidant mixture in an amount of coating;
[0101] In the electrodeposition solution, set the temperature to 42°C and the current density to 10A / dm -2 , direct current electrodeposition plating for 2.5 min, cleaning the surface, and then heat treating at 200 °C for 22 min in nitrogen to obtain a pretreated stainless steel strip;
[0102] The cleaning solution includes the following components: 3wt% citric acid, 9wt% phosphoric acid, and the remainder water;
[0103] The antioxidant mixture comprises the following ingredients: 3.5wt% sodium chloride, 3.5wt% citric acid, 2wt% L-cysteine, and the remainder is water;
[0104] The electrodeposition solution comprises the following components: 200 g / L nickel chloride, 20 g / L cerium chloride, 20 g / L nano silicon dioxide, 5 g / L nano carbon nitride-organic framework composite material, 3 g / L potassium fluorozirconate, 2 g / L citric acid, 60 mL / L hydrochloric acid, and the rest is water;
[0105] S3: The pretreated stainless steel strip is gas nitrided at a working gas pressure of 0.01 MPa and a temperature of 450° C. for 19 hours to obtain a highly corrosion-resistant stainless steel.
[0106] Comparative Example 3: The nano carbon nitride-organic skeleton composite material is not modified by using sulfonic acid polyaspartic acid, and the rest is the same as Example 1:
[0107] Step 1: Preparation of modified nano carbon nitride:
[0108] Take 6g of melamine, heat to 550°C, calcine for 2.3h, cool to 28°C, grind, add to 500mL of anhydrous ethanol, stir evenly, add 2.5g of octadecyltrichlorosilane, stir for 3.5h, centrifuge, wash, remove the supernatant, and dry to obtain modified nano carbon nitride;
[0109] Step 2: Preparation of organic framework materials:
[0110] Take 8g of sodium fumarate and 125mL of deionized water, stir evenly to obtain a sodium fumarate solution; take 9.5g of aluminum nitrate nonahydrate and 125mL of deionized water, stir evenly, add the sodium fumarate solution dropwise, continue stirring for 12min, filter, wash, and dry to obtain an organic framework material;
[0111] Step 3: Preparation of nano carbon nitride-organic framework composite materials:
[0112] Take 1g of organic framework material and 100mL of Tris-HCl buffer, and perform ultrasonic dispersion to obtain a dispersion; take 1.4g of dopamine hydrochloride and 200mL of Tris-HCl buffer, stir evenly, add the dispersion, perform ultrasonic dispersion for 21min, and then stir for 6.5h, add 0.5g of modified nano-carbon nitride, stir for 4h, wash, filter, and dry to obtain a nano-carbon nitride-organic framework composite material;
[0113] Step 4: Preparation of high corrosion resistant stainless steel:
[0114] S1: subjecting the stainless steel strip to solid solution treatment, flattening, and rolling to obtain a rolled stainless steel strip;
[0115] S2: Place the rolled stainless steel strip in the cleaning solution, set the temperature to 57°C, and perform ultrasonic cleaning for 4 minutes; rinse again with deionized water and blow dry with nitrogen; 2 Apply the antioxidant mixture in an amount of coating;
[0116] In the electrodeposition solution, set the temperature to 42°C and the current density to 10A / dm -2 , direct current electrodeposition plating for 2.5 min, cleaning the surface, and then heat treating at 200 °C for 22 min in nitrogen to obtain a pretreated stainless steel strip;
[0117] The cleaning solution includes the following components: 3wt% citric acid, 9wt% phosphoric acid, and the remainder water;
[0118] The antioxidant mixture comprises the following ingredients: 3.5wt% sodium chloride, 3.5wt% citric acid, 2wt% L-cysteine, and the remainder is water;
[0119] The electrodeposition solution comprises the following components: 200 g / L nickel chloride, 20 g / L cerium chloride, 20 g / L nano silicon dioxide, 5 g / L nano carbon nitride-organic framework composite material, 3 g / L potassium fluorozirconate, 2 g / L citric acid, 60 mL / L hydrochloric acid, and the rest is water;
[0120] S3: The pretreated stainless steel strip is gas nitrided at a working gas pressure of 0.01 MPa and a temperature of 450° C. for 19 hours to obtain a highly corrosion-resistant stainless steel.
[0121] experiment:
[0122] The high corrosion-resistant stainless steel prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was tested for performance. The sample was used as the working electrode, the calomel electrode was used as the reference electrode, the platinum electrode was used as the auxiliary electrode, the electrochemical etching solution was a 3.5% sodium chloride aqueous solution, the scanning potential speed was 2 mv / s, and the sample area was 1 cm 2 , detect the corrosion current density of stainless steel; refer to GB / T6459-86, conduct acetic acid salt spray test on the sample, pH value is 3.2, test temperature is 35℃, deposition amount is 1.5ml / h, test time is 96h, detect the corrosion rate of the sample, and the data obtained are shown in the following table:
[0123]
[0124] Conclusion: From the comparison of the data in the table, it can be seen that in Comparative Example 1, no nano carbon nitride is added, and the corrosion resistance is deteriorated. In Comparative Example 2, polyaspartic acid is not modified with sulfonic acid groups, and the dispersion effect of the nano carbon nitride-organic skeleton composite material is deteriorated, thereby affecting the corrosion resistance of stainless steel. In Comparative Example 3, sulfonic acid polyaspartic acid is not used to modify the nano carbon nitride-organic skeleton composite material, and the dispersion effect of the nano carbon nitride-organic skeleton composite material is poor, and the deposition effect of zirconium on the surface of the stainless steel strip is poor, thereby deteriorating the corrosion resistance. In Examples 1 to 3 of the present invention, stainless steel is treated with an electrodeposition liquid, and a coating containing nickel, cerium, nano silicon dioxide, nano carbon nitride-organic skeleton composite material, and zirconium is electrodeposited on the surface of the stainless steel, thereby enhancing the corrosion resistance of corrosion-resistant stainless steel. In Examples 1-3 of the present invention, polyaspartic acid is modified with sulfonic acid groups. The introduction of sulfonic acid groups can improve the dispersion performance of polyaspartic acid, and the nano carbon nitride-organic skeleton composite material is modified with sulfonic acid polyaspartic acid, thereby improving the dispersion effect of the nano carbon nitride-organic skeleton composite material. Potassium fluorozirconate is added to the electrodeposition solution, and the addition of polyaspartic acid on the nano carbon nitride-organic skeleton composite material promotes the deposition of zirconium element, so that zirconium element is deposited on the surface of the stainless steel strip, further enhancing the corrosion resistance of the stainless steel strip.
[0125] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A processing technology for highly corrosion-resistant stainless steel, characterized in that: The following steps are involved: Step 1: subjecting the stainless steel strip to solid solution treatment, flattening, and rolling to obtain a rolled stainless steel strip; Step 2: Place the rolled stainless steel strip in a cleaning solution, set the temperature to 55-60°C, and perform ultrasonic cleaning for 3-5 minutes; rinse again with deionized water, and blow dry with nitrogen; Coating an anti-oxidation mixed solution on the surface; performing direct current electrodeposition electroplating for 2-3 minutes in an electrodeposition solution, cleaning the surface, and then heat treating under nitrogen for 20-25 minutes to obtain a pretreated stainless steel strip; Step 3: gas nitriding the pretreated stainless steel strip at a working pressure of 0.01 MPa and a temperature of 450°C for 18-20 hours to obtain a highly corrosion-resistant stainless steel; The electrodeposition solution comprises the following components: 200-210 g / L nickel chloride, 20-22 g / L cerium chloride, 20-23 g / L nano silicon oxide, 5-7 g / L nano carbon nitride-organic framework composite material, 3-4 g / L potassium fluorozirconate, 2-2.5 g / L citric acid, 60-65 mL / L hydrochloric acid, and the rest is water; The preparation method of the nano carbon nitride-organic skeleton composite material is as follows: taking an organic skeleton material and a Tris-HCl buffer, ultrasonically dispersing to obtain a dispersion; taking dopamine hydrochloride and a Tris-HCl buffer, stirring evenly, adding the dispersion, ultrasonically treating for 20-22 minutes, stirring for 6-7 hours, adding modified nano carbon nitride, stirring for 2-3 hours, adding sulfonic acid polyaspartic acid, heating to 45-50° C., reacting for 5-6 hours, washing, filtering, and drying to obtain the nano carbon nitride-organic skeleton composite material; The preparation method of the organic framework material is as follows: sodium fumarate and deionized water are taken, stirred evenly to obtain a sodium fumarate solution; aluminum nitrate nonahydrate and deionized water are taken, stirred evenly, the sodium fumarate solution is added dropwise, stirring is continued for 10-15 minutes, filtering, washing and drying to obtain the organic framework material.
2. The processing technology of a highly corrosion-resistant stainless steel according to claim 1 is characterized in that: The preparation method of the sulfonic acid polyaspartic acid is as follows: maleic anhydride, sodium 2-aminoethanesulfonate and ammonium carbonate are mixed evenly, deionized water is added, and the mixture is irradiated for 5-6 minutes, sodium hydroxide solution is added, the mixture is stirred evenly, and the mixture is irradiated for 3-4 minutes, hydrochloric acid is used to adjust the pH value of the solution to 2-3, and the mixture is precipitated, filtered and dried to obtain the sulfonic acid polyaspartic acid.
3. The processing technology of a highly corrosion-resistant stainless steel according to claim 1 is characterized in that: The preparation method of the modified nano carbon nitride is as follows: taking melamine, heating it to 545-555° C., calcining it for 2-2.5 hours, cooling it to 25-30° C., grinding it, adding it to anhydrous ethanol, stirring it evenly, adding octadecyltrichlorosilane, stirring it for 3-4 hours, centrifuging it, washing it, removing the supernatant, and drying it to obtain the modified nano carbon nitride.
4. The processing technology of a highly corrosion-resistant stainless steel according to claim 1 is characterized in that: The cleaning solution includes the following components: 3wt% citric acid, 9wt% phosphoric acid, and the remainder is water.
5. The processing technology of high corrosion-resistant stainless steel according to claim 1 is characterized in that: The antioxidant mixed solution includes the following components: 3.5 wt % sodium chloride, 3.5 wt % citric acid, 2 wt % L-cysteine, and the rest is water.
6. High corrosion-resistant stainless steel obtained by processing according to the processing technology of high corrosion-resistant stainless steel according to any one of claims 1 to 5.
Citation Information
Patent Citations
Preparation method for metallic matrix surface corrosion-resistant nano-film
CN108396353A
Corrosion-resistant stainless steel band and processing technology thereof
CN115354272A